DESIGNING ANDROID APPLICATION “LEARN ENGLISH BETTER” FOR CHILDREN’S SPEAKING SKILL AT JUNIOR HIGH SCHOOL - Agustina, Ulfa Wulan; Muslimah, Khairunnisa Nur (JoEMS (Journal of Education and Management Studies), 2021)
Being able to communicate in English fluently is the concern of every individual in this world because it gives some advantages in this life. As mobile technology has grown rapidly in educational sector, it creates new opportunities for improving learning experience of students in every level. The purpose of this research is to improve students speaking skill through LEB (Learning English Better) app. This study was conducted to fix the concern by concertating on how android application as learning media are used in speaking class of the eight grade of junior high school. This research combined the steps of R&D with the ADDIE model. The data were obtained from questioners and observation. The research was conducted in SMP Darul UlumKepuhdoko. The findings shows that LEB app get 3.1 point which categorized fair and worth to use in media validation and get 4 point which categorized fair and worth to use in material validation and also get 4.2 point in the assessment result by respondence wich is category good and worth to use. The result of this study shows that LEB app was appropriate to eight grade of SMP Darul Ulum students to learn speaking skill. Based on principle of m-learning, LEB app is flexible and practical. The product is easy to operate simple and helpful to learn English speaking skill